Respon Hasil Tanaman Tomat (Lycopersicon esculentum) Terhadap Pemberian Paclobutrazol dan Dosis Pupuk NPK - Sugiharto, Nella Oktavianty; Augustien K., Nora; Sulistyono, Agus (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Brawijaya, 2023)
Tomato is a type of horticultural commodity that is quite in demand by the people of Indonesia because of its high nutritional content. The aims of this research is to determine the effect of paclobutrazol concentration and dose of NPK fertilizer on the yield of tomato plants. This research was conducted on the experimental garden of the Faculty of Agriculture, University of National Development